2022
DOI: 10.1371/journal.ppat.1010316
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma virus lacking the host range determinant M062 stimulates cGAS-dependent type 1 interferon response and unique transcriptomic changes in human monocytes/macrophages

Abstract: The evolutionarily successful poxviruses possess effective and diverse strategies to circumvent or overcome host defense mechanisms. Poxviruses encode many immunoregulatory proteins to evade host immunity to establish a productive infection and have unique means of inhibiting DNA sensing-dependent type 1 interferon (IFN-I) responses, a necessity given their dsDNA genome and exclusively cytoplasmic life cycle. We found that the key DNA sensing inhibition by poxvirus infection was dominant during the early stage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 77 publications
(152 reference statements)
0
20
0
Order By: Relevance
“…In myxoma virus, these genes have evolved to have distinct protein interaction partners after duplication ( 66 68 ). For example, only M062 has been shown to interact with sterile alpha motif domain-containing protein 9 (SAMD9) and thereby inhibit a cGAS-dependent interferon response ( 67 , 69 ). A recent study identified a similar example of duplication in cetacean poxvirus in which the virus genome was predicted to encode two tandem copies of the E3L ortholog, a full-length copy (CePV-TA-20) and a truncated copy (CePV-TA-21), which lacks the amino-terminal Zα domain ( 70 , 71 ).…”
Section: Gene Duplicationsmentioning
confidence: 99%
“…In myxoma virus, these genes have evolved to have distinct protein interaction partners after duplication ( 66 68 ). For example, only M062 has been shown to interact with sterile alpha motif domain-containing protein 9 (SAMD9) and thereby inhibit a cGAS-dependent interferon response ( 67 , 69 ). A recent study identified a similar example of duplication in cetacean poxvirus in which the virus genome was predicted to encode two tandem copies of the E3L ortholog, a full-length copy (CePV-TA-20) and a truncated copy (CePV-TA-21), which lacks the amino-terminal Zα domain ( 70 , 71 ).…”
Section: Gene Duplicationsmentioning
confidence: 99%
“…Although early gene expression of this virus did not show significant difference from that of the wildtype MYXV, 10,20 ΔM062R infection failed to lead to host shutoff (Figure 1B).…”
Section: Resultsmentioning
confidence: 92%
“…HeLa cells were transfected with the plasmid containing the luciferase expression cassette driven by one of following VACV intermediate gene promoters, pA2L, 24 pI1L, 24 and VACV intermediate consensus promoter sequence (pINT) 25 (M. Wiebe, University of Nebraska-Lincoln) using ViaFect (Cat# E4982, Promega, Madison, WI) at 0.8 µg/mL with the transfection agent to DNA ratio of 3 µL to 1 µg as previously described. 20 Next Generation RNA sequencing THP-1 cells (10 6 cells per 3.5 cm dish) were differentiated in PMA at 50 ng/mL for up to 48 hours before mock treated, transfection with interferon stimulated DNA (ISD) 47 Dual-RNAseq bioinformatic data processing and GO:BP analyses A dual-RNAseq bioinformatic data processing pipeline was utilized for the study as previously described. 20 Exploratory data analysis (EDA) and differential expression analysis was performed using R and DESeQ2 v1.32.0, where p-value and adjusted pvalue thresholds were set to 0.05 and 0.1, respectively.…”
Section: Luciferase Assay To Examine Viral Intermediate Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, C7L-like host range proteins from other poxviruses contribute to their host and cellular tropism [10] . Functional and structural studies of these C7-like proteins demonstrated that some of them bind and antagonize host sterile alpha-motif domain-containing 9 protein to overcome type-I IFN-mediated host restriction 11 , 12 , 13• . Thus, poxvirus-encoded proteins known as host range factors can dictate which cells, tissues, or hosts they can productively infect.…”
Section: Host-restricted and Zoonotic Infection Of Poxvirusesmentioning
confidence: 99%